Changes in apoptosis of human polymorphonuclear granulocytes with aging - Fülöp Jr, T; Fouquet, C; Allaire, P; Perrin, N; Lacombe, G; Stankova, J; Rola-Pleszczynski, M; Gagné, D; Wagner, J.R; Khalil, A; Dupuis, G (Mechanisms of ageing and development, 1997)
Many alterations with aging occur at the cellular and organic levels in the immune system ultimately leading to a decrease in the immune response. Our aim in the present work was to study apoptosis of polymorphonuclear granulocytes (PMN) with aging under various stimulations since apoptosis might play an important role in several pathologies encountered with aging. The PMN of healthy young (20–25 years) and elderly (65–85 years) subjects were examined after 24 h of sterile culture with and without stimulation. The stimulating agents included: phorbol myristate acetate (PMA), hydrogen peroxide (H2O2), N-formyl-methionyl-leucyl phenylalanine (FMLP), granulocyte-macrophage colony stimulating factor (GM-CSF), reduced glutathione (GSH), lipopolysaccharide (LPS) and interleukin 2 (IL-2). Apoptosis was assessed by traditional staining of the plates, by flow cytometric staining and DNA gel electrophoresis. It was found that without stimulation the susceptibility of PMN to apoptosis was slightly increased with aging. Under various stimulations, such as PMA, H2O2, apoptosis was almost 100%, while the treatment by FMLP, oxLDL and GSH did not change its extent in PMN obtained either from young or elderly subjects. Marked age-related changes were observed in the extent of apoptosis under stimulation with GM-CSF, IL-2 and LPS. These agents were able to significantly prevent apoptosis in PMN of young subjects, while only the GM-CSF was able to slightly modulate it in neutrophils of elderly subjects. From these results, we suggest that changes in apoptosis of PMN with aging could play a role in the increased incidence of certain immune system related pathologies of aging, such as cancer, infections and autoimmune disorders.